Translation, Adaption, and Psychometric Testing of the Myanmar Version of the Medical Outcomes Study Social Support Survey for People Living With HIV/AIDS - Huang, Feifei; Chen, Wei-Ti; Lin, Sai Htun; Tun, Min San; Nwe, Thet Wai; Oo, Yin Thet Nu; Oo, Htun Nyunt (Frontiers in Psychology, 2021)
Introduction: Valid and reliable instruments are crucial for measuring perceived social support among people living with HIV (PLHIV). We aimed to investigate the psychometric properties of the English version of the 19-item Medical Outcomes Study Social Support Survey (MOS-SSS) adapted for PLHIV in Myanmar. Methods: Based on a standard cross-cultural procedure, we adapted the MOS-SSS and formed a Myanmar version of the scale (MOS-SSS-M), and then tested its validity and reliability. A sample of 250 eligible PLHIV was collected from a closed Facebook group that included more than 10,000 Myanmars, most of whom were PLHIV. Results: The MOS-SSS-M achieved a Cronbach's α of 0.82 to 0.95. Confirmatory factor analysis revealed an acceptable fit index for the four-factor structure. Construct validity was demonstrated by significant association with self-reported HIV stigma and stress levels, and further confirmed by the findings of Rasch analysis. Conclusion: The MOS-SSS-M with a four-factor structure can be used to measure the level and categories of perceived social support among PLHIV in Myanmar.